The Influence of Electronic Word of Mouth (E-WOM), Website Quality, and Consumer Confidence on Purchasing Decisions (Study on Shopee E-Commerce Users in Surakarta) - Dwi Tantya, Ega Aulia; Rosyadi, Imron (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to explore the impact of Electronic Word-of-Mouth (E-WOM), website quality, and consumer trust on purchasing decisions on the Shopee e-commerce platform in Surakarta. Data was collected through a survey distributed to Shopee e-commerce users in Surakarta. Data analysis uses multiple linear regression methods to test the relationship between independent variables (E-WOM, website quality, and consumer trust) and the dependent variable (purchasing decisions). The research results show that E-WOM, website quality, and consumer trust have a significant positive influence on the purchasing decisions of Shopee e-commerce users in Surakarta. The implications of these findings emphasize the importance for e-commerce companies to pay attention to and improve service quality, strengthen consumer trust, and build a positive reputation in the context of E-WOM to improve purchasing decisions. These findings also provide valuable insights for marketing practitioners in designing effective and relevant marketing strategies to expand market share and increase customer satisfaction in today's digital era.